Hello here is a solution :
x²-8y-6x+y²=4....(1)
A)
x²-6x = x²-2(3)x+9-9
= x²-2(3)x+3²-9
x²-6x =(x-3)² -9
B)
y²-8y = y²-2(4)y +4²-16
y²-8y = (y-4)²-16
C)
in (1) :
(x-3)² -9 +(y-4)²-16 = 4
(x-3)² +(y-4)² = 29 ...<span>is the standard form of the equation
</span> <span>Select answer 1 :
</span><span>A: 3
B: 4
C: (x−3)2+(y−4)2=29</span>
Answer:
The slope is -2
Step-by-step explanation:
(-4,6) (3,-8)
(y₂ - y₁) / (x₂ - x₁)
((-8) - (6)) / ((3) - (-4))
(-8 - 6) / (3 + 4)
-14/7 = -2
_ * 5 > 5
3/3 is equal to 1 which would make them equal to each other.
2/3 is less than one which means it would make the number on the left less than 5, not greater than.
the answer is 5/3 because it is bigger than the other answer choices and will result in a greater number than that on the right.
Answer:
four tenths
Step-by-step explanation: